2014
DOI: 10.1002/jwmg.773
|View full text |Cite
|
Sign up to set email alerts
|

Survival, demography, and growth of gopher tortoises (Gopherus polyphemus) from three study sites with different management histories

Abstract: Recovery or sustainable management of wildlife populations often entails management of habitat on which they depend. In this regard, turtles pose unique conservation challenges because of their life histories. The combination of late maturity, low survival when young, and dependence on high adult survival suggests they may be slow to respond demographically to conventional habitat management. Thus, long‐term studies are necessary to understand population dynamics and recovery potential in these species. We use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 46 publications
3
41
1
Order By: Relevance
“…First, the observed and estimated population structure was characterized by an even sex ratio and a greater proportion of adults than juveniles. This structure is consistent with a general prediction for long-lived turtles, where high survival of adults followed by low postmaturity growth rates results in the accumulation of similar-sized adults from different age cohorts (Alford 1980); thus, greater abundance of adults than juveniles is a hypothesized characteristic of stable populations of long-lived turtles (Tuberville et al 2014). Second, regression analysis did not detect significant changes in observed adult body size during the course of the study, a result which was documented in the declining Oklahoma population (East et al 2013).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…First, the observed and estimated population structure was characterized by an even sex ratio and a greater proportion of adults than juveniles. This structure is consistent with a general prediction for long-lived turtles, where high survival of adults followed by low postmaturity growth rates results in the accumulation of similar-sized adults from different age cohorts (Alford 1980); thus, greater abundance of adults than juveniles is a hypothesized characteristic of stable populations of long-lived turtles (Tuberville et al 2014). Second, regression analysis did not detect significant changes in observed adult body size during the course of the study, a result which was documented in the declining Oklahoma population (East et al 2013).…”
Section: Discussionsupporting
confidence: 89%
“…Similarly, Tuberville et al (2014) recently suggested that greater abundance of adults than juveniles should be expected in stable populations of another long-lived turtle species, Gopher Tortoises (Gopherus polyphemus), but our analyses were somewhat inconsistent with this notion for M. temminckii. The stable population structure produced from population projection analysis was dominated by juveniles at Spring Creek and the two declining western populations.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…In contrast, 10 populations in northern peninsular Florida tended to have high proportions of tortoises in intermediate size classes (Alford ). We suspect our study population is at carrying capacity, resulting in higher dispersal and emigration of subadults, which may be disadvantaged in social interactions with larger adults (McRae et al b , Tuberville et al ). As implied by the very high apparent survival estimates for tortoises in the ruderal field, adults tortoises in Hill Garden exhibited a high degree of site fidelity.…”
Section: Discussionmentioning
confidence: 98%
“…Survival and recruitment of juvenile tortoises also affects population persistence [36]. We thus focused on juvenile growth as a proxy for understanding possible demographic responses to altered climate because, it responds more quickly to changing resources and habitat quality than many other demographic metrics [37]. Desert tortoises also exhibit behavioral plasticity, which allow them to alter metabolic expenditures based on water availability [2].…”
Section: Introductionmentioning
confidence: 99%